(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study investigated the impact of governance on moral behavior in small enterprises. The problem of the study was represented in that the principles of corporate governance are not applied in the small enterprises what leads to cause high risk to both those small enterprises and financial reporting users as well. The significance of the study is represented in that applying the principles of governance is of great importance for evaluating the current and the sustainable performance and for reducing the performance risk related to error, violation, and corruption and for dealing with unexpected crises. The study aimed to identify the impact of applying governance on work environment in the small enterprises and to enhance moral behavior in the small enterprises. The researcher adopted the descriptive analytical approach to verify the hypothesis: There is a statistically significant relationship between applying the principles of corporate governance and enhancing ethical behavior. The researchers concluded the following findings: There is a statistically significant relationship between applying the principles of governance and enhancing moral behavior. There is a statistically significant relationship between applying the principles of governance and performance risk related to error, violation and corruption and for dealing with unexpected crises in the small enterprises. The commitment to the principles of governance leads to the commitment to the moral behavior and to reaching innovative solutions. The researchers recommended the following: Principles of governance should be applied because they enhance moral behavior. Principles of governance should be applied in order to overcome performance risk related to error, violation and corruption and for dealing with unexpected crises in the small enterprises